Light spectrum preference of Nile Tilapia (Oreochromis niloticus) under different hunger levels - Jin, Guang; Zhao, Jian; Zhang, Yadong; Liu, Gang; Liu, Dezhao; Zhu, Songming; Shao, Yufang; Ye, Zhangying (International Journal of Agricultural and Biological Engineering, 2019)
In order to improve the light welfare of Nile tilapia in aquaculture, the influence of hunger level on light spectrum preference of Nile tilapia was explored in this study. The whole experiment was based on the emptying of the gastrointestinal contents, and carried out under the controlled laboratory conditions. The light spectrum preference was assessed by counting the head location of fish in each experimental tank, which containing seven compartments (i.e., red, blue, white, yellow, black, green and public area). t-Distributed Stochastic Neighbor Embedding (t-SNE) was adopted to visualize the hunger level-based dynamic preference on light spectrum in two-dimensional space. According to the clustering results, significant differences in light spectrum preferences of Nile tilapia, under the different hunger levels, were indicated. In addition, the average visit frequency in green compartment was significantly lower than that in other color compartments throughout the whole experiment, and the total visit frequency in red compartment was relatively higher during the whole experiment.Keywords: light welfare, Nile tilapia, hunger level, light spectrum preference, t-Distributed Stochastic Neighbor EmbeddingDOI: 10.25165/j.ijabe.20191205.4170Citation: Jin G, Zhao J, Zhang Y D, Liu G, Liu D Z, Zhu S M, et al. Light spectrum preference of Nile Tilapia (Oreochromis niloticus) under different hunger levels. Int J Agric & Biol Eng, 2019; 12(5): 51–57.